ACCIDENTAL FINDINGS OF ORAL PIGMENTATION, ITS CLINICAL PRESENTATION AND ASSOCIATION WITH SOME RISK FACTORS - Ali Anwaar; Sidra Saleem; Fareed Ahmad; M. Shairaz Sadiq; Muhammad Anwaar Alam; Saliha Abid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The diagnosis of oral pigmentation is challenging. Oral pigmentation can be physiological or pathological, endogenous, or exogenous. It can be presented as black, brown, white, and red in color.Objectives: This study aims to determine the prevalence and frequency of oral pigmentation and the factors causing these changes. The correlation between history (demographic data, habits, medical history) and clinical presentation (color, site, nature) of oral pigmentation will be calculated.Materials and Methods: A questionnaire and clinical examination is to be administered. First to predict the incidence of oral pigmentation as Accidental finding and then corresponding to the data, different types of oral pigmentation and color changes of oral mucosa are examined.Results: The Demographic feature of our study reveals that out of 300 sample candidates with 217 (72.3%) males and 83 (27.7%) females. 15.3% individuals from both genders belonged to the 14-25 years age group. The maximum number of candidates fell into the 26–35-year age group with 24%. 23.3% reported a history of smoking from all age groups whilst 7.3% referred to pan chewing.Conclusion: The data provided enlightens our knowledge of oral pigmentations, especially accidental findings when a patient is presented with another dental disease. Although some of the lesions were innocuous yet the dentist should be able to recognize the lesion for a Differential Diagnosis and should refer the patient to a specialist for further investigation and treatment before a lesion may become malignant